2014
DOI: 10.1371/journal.pone.0087058
|View full text |Cite
|
Sign up to set email alerts
|

Understanding a Substrate’s Product Regioselectivity in a Family of Enzymes: A Case Study of Acetaminophen Binding in Cytochrome P450s

Abstract: Product regioselectivity as influenced by molecular recognition is a key aspect of enzyme catalysis. We applied large-scale two-dimensional (2D) umbrella sampling (USP) simulations to characterize acetaminophen (APAP) binding in the active sites of the family of Cytochrome P450 (CYP) enzymes as a case study to show the different regioselectivity exhibited by a single substrate in comparative enzymes. Our results successfully explain the experimentally observed product regioselectivity for all five human CYPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 72 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Additionally, a recent computational study by Yang et al . [ 74 ] suggested Asn 312 , Asp 313 , and Phe 260 to be critical for binding of acetominophen to CYP 1A2.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a recent computational study by Yang et al . [ 74 ] suggested Asn 312 , Asp 313 , and Phe 260 to be critical for binding of acetominophen to CYP 1A2.…”
Section: Resultsmentioning
confidence: 99%
“…A study of cytochrome P450 (CYP) enzymes revealed that a large binding pocket results in less direct ligand‐protein interactions and a relatively fast interconversion between different binding states, resulting in low regioselectivity . The situation is even worse for most LPMOs as they have to rely on a binding surface instead of a pocket to accommodate the very large substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that cytochrome P450 enzymes can regulate cell proliferation (43,44). APAP interacts with the active sites of cytochrome P450 enzymes related to APAP-induced cytotoxicity (45,46). Many studies have shown that APAP-induced cytotoxicity requires bioactivation by cytochrome P450 enzymes (47,48), and APAP can induce the apoptotic death pathway by increasing cytochrome P450 activity (34).…”
Section: Discussionmentioning
confidence: 99%